138k views
1 vote
Using ƒ(x) = 2x + 7 and g(x) = x − 3, find ƒ(g(-2)).

User BrainLoop
by
5.0k points

1 Answer

3 votes

Answer: -3

Explanation:

For this problem, it is asking for f(g(-2)). This means g(-2) is plugged into every x in f(x). Therefore, we will first find g(-2).

g(-2)=-2-3

g(-2)=-5

Now that we have g(-2), we can plug it into f(x).

f(-5)=2(-5)+7

f(-5)=-10+7

f(-5)=-3

User Joeklieg
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.